2019
DOI: 10.4194/1303-2712-v19_5_02
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A 60 days feeding trial was conducted to study the effects of dietary alginic acid (AA) on growth and haemato-immunological responses in Cirrhinus mrigala fingerlings. One hundred eighty fingerlings were randomly distributed into five treatments in triplicates. Five diets were prepared with graded level of alginic acid and were designated as: control (Basal feed + 0% AA), T1 (Basal feed + 0.2% AA), T2 (Basal feed + 0.4% AA), T3 (Basal feed + 0.6% AA) and T4 (Basal feed + 0.8% AA). Higher weight gain % and spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…[4] There is extensive use of AA in the food industry and healthcare, including food DOI: 10.1002/mnfr.202300130 additives, thickeners, and excipients in medicines, suggesting a high probability of AA exposure. [5] Previous studies reported that AA has biological activities such as anti-allergic effects mediated by inhibiting mast cell-mediated allergic reactions and histamine release, [6,7] immunomodulatory effects mediated by increasing serum complement and lysozyme concentrations, [8,9] and anti-inflammatory effects mediated by reducing tissue edema and inhibiting the release of proinflammatory cytokines. [10][11][12] Although numerous studies showed the positive effects of AA, relatively little research has been carried out on the reproduction of female mammals, even less in sows.…”
Section: Introductionmentioning
confidence: 99%
“…[4] There is extensive use of AA in the food industry and healthcare, including food DOI: 10.1002/mnfr.202300130 additives, thickeners, and excipients in medicines, suggesting a high probability of AA exposure. [5] Previous studies reported that AA has biological activities such as anti-allergic effects mediated by inhibiting mast cell-mediated allergic reactions and histamine release, [6,7] immunomodulatory effects mediated by increasing serum complement and lysozyme concentrations, [8,9] and anti-inflammatory effects mediated by reducing tissue edema and inhibiting the release of proinflammatory cytokines. [10][11][12] Although numerous studies showed the positive effects of AA, relatively little research has been carried out on the reproduction of female mammals, even less in sows.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28] Alginic acid have widespread applications in the food / chemical industries, medical sector, water treatment plants, packaging materials and cell immobilization. [29][30][31][32][33] In the chemical industry, alginic acid is primarily used as a heterogeneous Brønsted acid promoter. [34,35] The manipulated alginate materials like alginic acid supported organometallic catalysts or metal ions or nanoparticles can perform significant catalysis in various chemical transformations.…”
Section: Introductionmentioning
confidence: 99%
“…It is extensively used in products for human consumption due to biocompatibility, high stability, biodegradability, flocculation and gel formation ability at lower pH values [25–28] . Alginic acid have widespread applications in the food / chemical industries, medical sector, water treatment plants, packaging materials and cell immobilization [29–33] . In the chemical industry, alginic acid is primarily used as a heterogeneous Brønsted acid promoter [34,35] .…”
Section: Introductionmentioning
confidence: 99%